Party food art - Peterson, Tamara J. M., 1972- (North Mankato, Minn. : Capstone Press, 2025)
"Ready to make your celebrations spectacular? Unleash your inner food artist! Transform everyday ingredients into party foods that look beautiful and taste even better. Build a chips and dip stadium to watch the big game. Turn blue gelatin into a pool party in a cup. Make tiny teacakes for a spa party. What food art will you create?"--Provided by the publisher.
Transforming ingredients into food art! -- Kitchen tips -- BBQ party watermelon skewers -- Ocean party sea star snacks -- Backyard bug party caterpillar crates -- Gaming party video game charcuterie -- Pool party bear fun floaties -- Movie marathon party munchie boxes -- Sports party snack stadium -- Sleepover party sleeping bag wrap snacks -- Glamping party taquito campfires -- Carnival party big top cups -- Tie-dye party groovy popsicles -- Pirate party treasure chest -- Tea party mini cakes.
Includes bibliographical references (p. 32).
4-8
750
3-4.
3-5.
Keywords: Parties; Cooking